The Effect of Fractional Reserve Banking on the Risk of Failure in State-Owned Conventional and Sharia Banks in Indonesia 2021-2024 - Ni Made Ayu Puspa Dewi; Christimulia Purnama Trimurti; Ni Luh Putu Suarmi Sri Patni (LPPM Universitas Dhyana Pura, 2026)
A bank is an intermediary between entities with surplus funds and those with deficits. Bank operations may involve the risk of failure. Banks act as institutions that collect and distribute funds based on the financial intermediary theory. This study aimed to examine the effect of Fractional Reserve Banking on the risk of failure in conventional and Islamic banks. The research method uses a descriptive-quantitative approach, with a purposive sampling method. The study found that the results of multivariate tests (Pillai's Trace, Wilks' Lambda, Hotelling's Trace, Roy's Largest Root) showed a significance value <0.05. The hypothesis test FRB significantly affects ROA and LDR/FDR. The Difference Test (t-test) found no significant differences between Conventional Banks and State-Owned Sharia Banks for the variables STLR, GWM, FR, ROA, and LDR/FDR. Conclusion: Fractional Reserve Banking (FRB) is proven to have a significant effect on the risk of bank failure, and there is no significant difference between the financial ratios of Conventional Banks and State-Owned Sharia Banks. Add the contribution of the results of your study The research results show that although conventional and Islamic banks employ different financing methods, their performance in terms of liquidity, financing distribution, and profitability is relatively similar. This suggests that the use of fractional reserve banking principles in both types of banks does not significantly impact the risk of bank failure. These findings can serve as a reference for regulators and the public when choosing banking services.